A case of eosinophilic pneumonia simultaneously diagnosed in a patient and a tame cat: a case report - Tsuji, Takao (BioMed Central, 2014)
INTRODUCTION: Chronic eosinophilic pneumonia is an idiopathic disorder of unknown etiology. Corticosteroid treatment provides a good response but recurrence frequently occurs after tapering of corticosteroid. Chronic eosinophilic pneumonia occurs predominantly in middle-aged women and non-cigarette smokers, which leads to the speculation that environmental antigens, particularly in the home, contribute to the etiology. CASE PRESENTATION: A 66-year-old Japanese woman was given a diagnosis of chronic eosinophilic pneumonia for 8 years and was treated with prednisone. She developed respiratory symptoms again with tapering of prednisone (10mg/day). A chest radiograph revealed patchy shadows in her bilateral upper lung fields, and bronchoalveolar lavage fluid revealed marked eosinophilia. Based on negative findings for other causes of eosinophilia, the diagnosis of the recurrence of chronic eosinophilic pneumonia was established. She was treated with prednisone (20mg/day), which demonstrated rapid improvement. Around the same time, her tame cat developed oral breathing, tachypnea and peripheral eosinophilia. Chest radiography of the cat revealed ground-glass opacity in its bilateral upper lung fields. Eosinophilic pneumonia was also diagnosed in the cat that was treated by prednisone (3mg/day). Since eosinophilic pneumonia was diagnosed simultaneously in the patient and her tame cat, it can be suggested that inhaled environmental antigens in the home caused the eosinophilic pneumonia. After moving out of her home, she and the cat had no recurrence of eosinophilic pneumonia. CONCLUSIONS: Although chronic eosinophilic pneumonia is an idiopathic disorder of unknown etiology, our case suggests that inhaled environmental antigens in the home may be associated with the causes of chronic eosinophilic pneumonia. A pet’s disease may give us an important clue for the therapeutic approach of the owner’s disease.